Correspondence of Erasmus. - Erasmus, Desiderius, -1536 (Erasmus, Desiderius, -1536. Works. 1974 ;, 2012)
This volume contains the surviving correspondence of Erasmus for the first seven months of 1529. For nearly eight years he had lived happily and productively in Basel.